Analysis of Supply Chain Pattern and Added Value of Processed Catfish (Clarias sp) Agroindustry in Hangtuah Village, Perhentian Raja Sub District, Kampar Regency, Riau Province - Yunita Feronika Br. Silaban; Hendrik Hendrik; Clara Yolandika (Jurnal Perikanan dan Kelautan, 2024)
Hangtuah Village is known as "Kampung Lele"; one of the business actors who run the catfish processing business is the Mina Sejahtera Group. This research was conducted in October 2023 in Hangtuah Village, Perhentian Raja District, Kampar Regency, Riau Province. This research aims to identify the supply chain pattern for catfish crackers and analyze the added value of catfish crackers in the Mina Sejahtera Group. The research method uses a survey method, and data is analyzed qualitatively and quantitatively. The research results show that the supply chain actors consist of partner farmers as suppliers of raw materials for catfish, the Mina Sejahtera Group as business actors and processors of catfish crackers, and consumers as buyers. Supply chain flows include product flows, financial flows, and information flows. The condition of the supply chain for catfish crackers in Hangtuah Village is based on the Food Supply Chain Network (FSCN) approach, which is seen from the supply chain targets, supply chain structure, supply chain entities, supply chain management, supply chain resources, and supply chain business processes that have been integrated with Good. The added value of processing catfish crackers is IDR 11.600/kg with a value-added ratio of 45,3%. The average profit given in the catfish processing process is IDR 5.600/kg or 48,2% of the product's added value, meaning that every kilogram of fresh catfish raw material processed can provide a profit of IDR 5,600/kg in added value.